THE EFFECT OF SURVEY, QUESTION, PREDICT, READ, RESPON AND SUMMARIZE (SQP2RS) ON STUDENTS’ READING COMPREHENSION OF THE TENTH GRADE STUDENTS OF SMK SWASTA ABDI NEGARA BINJAI AT ACADEMIC YEAR 2019/2020 - Efrini Panjaitan; Juliantina . (Jurnal Education and Development, 2020)
This study aimed to find out whether using survey, question, predict, read, respond and summarize (SQP2RS) effect on students’ reading comprehension of the tenth-grade students of SMK Swasta Abdi Negara Binjai at academic year 2019/2020. This Research used experimental research that involved into two groups: experimental group and control group. The experimental and control group are consisting of tenth grade students of SMK Swasta Abdi Negara Binjai. An experimental group received a new treatment that is SQP2RS while control group received a usual treatment. The population of this research is 133 students that consist of the 5 major and the sample is 48 students which consist of 25 students for experiment class and 23 students for control class. The writer used multiple choice tests as the instrument of collecting data. The data was analyzed by using t-test formula. Based on the data analysis, it was found that the value of t-observed (t0) was higher than the value of t-table (4.099 > 1.990; df = 78). It means that the hypothesis alternative (Ha) is accepted which shows that SQP2RS strategy significantly affects the students’ reading comprehension at SMK swasta abdi negara binjai at academic year 2019/2020.